Urinary Tract Infection and Associated Factors among Pregnant Women Receiving Antenatal Care at a Primary Health Care Facility in the Northern Region of Ghana - Vicar, Ezekiel K.; Acquah, Samuel E. K.; Wallana, Williams; Kuugbee, Eugene D.; Osbutey, Emmanuel K.; Aidoo, Abigail; Acheampong, Emmanuel; Mensah, Gloria Ivy (International Journal of Microbiology, 2023)
Urinary tract infection (UTI) is frequently encountered during pregnancy and is associated with adverse maternal, fetal, and neonatal effects. However, very little information is available on the prevalence of UTI among pregnant women in the northern part of Ghana, a region with a high birth rate. This study employed a cross-sectional analysis of the prevalence, antimicrobial profile, and risk factors associated with UTI in 560 pregnant women attending primary care for antenatal check-ups. Sociodemographic obstetrical history and personal hygiene information were obtained using a well-structured questionnaire. Afterward, clean catch mid-stream urine samples were collected from all participants and subjected to routine microscopy examination and culture. Of 560 pregnant women, 223 cases (39.8%) were positive for UTI. There was a statistically significant association between sociodemographic, obstetric, and personal hygiene variables and UTI (p<0.0001). Escherichia coli (27.8%) was the commonest bacterial isolate followed by CoNS (13.5%) and Proteus species (12.6%). These isolates exhibited greater resistance to ampicillin (70.1–97.3%) and cotrimoxazole (48.1–89.7%) but were fairly susceptible to gentamycin and ciprofloxacin. Gram-negative resistance to meropenem was up to 25.0%, and Gram positives resistance to cefoxitin and vancomycin was up to 33.3% and 71.4% respectively. The current findings extend our knowledge of the high frequency of UTIs and associated risk factors in pregnant women with E. Coli being the predominant and usual isolate. Variation existed in the resistance pattern of isolates to various drugs, underscoring the need to perform urine culture and susceptibility before treatment.